GROWTH INCIDENCE OF CANDIDA ALBICANS BY ACTIVITIES LACTIC ACID BACTERIA FROM FERMENTATION MILK PRODUCT - KLATEN, STIKES DUTAGAMA (STIKES DUTAGAMA KLATEN, 2018)
Fermented milk is milk that has been fermented by inoculation of starter culture of lactic acid-producing bacteria. BAL has a wide distribution and growing ability on various organic substrates and conditions such as acidic, alkaline, low temperature, high temperature, high salt, anaerobic conditions. In this study aims to determine the antifungal power of Candida albicans growth. Tests were conducted on samples taken from the Village Blanceran Karanganom Klaten. Candida albicans is a species of fungus that causes cutaneous and mucosal candidiasis. Until recently, treatment of candidiasis has depended on the use of oral or topical antibiotics. As an alternative therapy, some researchers recommend the use of probiotics, so the use of antibiotics can be reduced. The results show that there is no zone of resistance to Candida albicans this is because BAL still has nutrients to grow in the well and has not come out to inhibit the growth of Candida albicans. BAL can not directly shake and required isolation first.